О растительных примесях в лепной посуде финального неолита и бронзового века на территории Беларуси - Лошенков, М.И. (Археологія і давня історія України, 2017)
Статья вводит в научный оборот новые данные ботанического содержания с памятников неолита и бронзового века Беларуси. Включения зерна культурных видов (ячмень, пшеница, просо, горох, боб) зафиксированы в лепной посуде 13 поселений. На одном — Кривина Первая — найдены минерализованные семена льна. Документальные факты маркируют начало зарождения земледелия в республике примерно в последней четверти III тыс. до н. э. У статті представлена невелика колекція ботанічних знахідок з 14 пам'яток археології на території Білорусі. Хронологічні рамки поселень — пізній неоліт — бронзовий вік (друга половина III тис. до н. е. — VIII ст. до н. е.). Автор вважає, що культуру землеробства племенам півдня лісового неоліту на територію Білорусі принесло змішане населення (трипільсько-дніпро-донецьке) з розвинених землеробських осередків в Україні. Зародження землеробства в республіці відбувалося десь у другій половині III — II тис. до н. е. There are small collections of botanic findings from the 14 archaeological monuments on the territory of Belarus. Chronological frames of settlements — the late Neolithic — the Bronze age (the second half of 3 thousand BC — 7 century BC). There are found the inclusion of grains and seeds of cultivated species (19) on the 13 archaeological monuments: barley (Hordeum vulgare L.), wheat (Triticum aestivum L.), millet (Panicum miliaceum L.), bean (Vicia faba L.) and pea (Pisum sativum L.). There are seeds of related weeds (4): fire field (Bromus arvensis L.), grekiska vonkova (Fallopia convolvulus (L.) A. Löve), wild oat (Avena fatua L.) or rye (Secale cereale L.). Paleobotanical spectrum of the settlement of Old Yurkovichi consists of barley (3) wheat (3), millet (4), peas (1). Mineralized lesema (Linum usitatissimum L.) was found in the lower lay ofpeatland of the settlement Krivina I. The author considers that the culture of agriculture was brought to the tribes of the South forest Neolithic on the territory of Belarus from developed agricultural centers in Ukraine by a mixed population (Tripolye—Dnieper-Donets). On the territory of Belarus the origination of the agriculture was during the second part of the 3—2 BC.